Weaknesses in the reporting of cross-sectional studies according to the STROBE statement the case of metabolic syndrome in adults from Peru (Colombia Medica, 2015)
Introduction:The inadequate reporting of cross-sectional studies, as in the case of the prevalence of metabolic syndrome, could cause problems in the synthesis of new evidence and lead to errors in the formulation of public policies.Objective:To evaluate the reporting quality of the articles regarding metabolic syndrome prevalence in Peruvian adults using the STROBE recommendations.Methods:We conducted a thorough literature search with the terms "Metabolic Syndrome", "Sindrome Metabolico" and "Peru" in MEDLINE/PubMed, LILACS, SciELO, LIPECS and BVS-Peru until December 2014. We selected those who were population-based observational studies with randomized sampling that reported prevalence of metabolic syndrome in adults aged 18 or more of both sexes. Information was analysed through the STROBE score per item and recommendation.Results:Seventeen articles were included in this study. All articles met the recommendations related to the report of the study's rationale, design, and provision of summary measures. The recommendations with the lowest scores were those related to the sensitivity analysis (8%, n= 1/17), participant flowchart (18%, n= 3/17), missing data analysis (24%, n= 4/17), and number of participants in each study phase (24%, n= 4/17).Conclusion:Cross-sectional studies regarding the prevalence of metabolic syndrome in peruvian adults have an inadequate reporting on the methods and results sections. We identified a clear need to improve the quality of such studies.